Continuous Flow Microreactor Promoted the Catalytic N-Oxidation Reaction of Pyridine Derivatives - Chen, Siyuan; Yang, Shanxiu; Wang, Hao; Niu, Yanning; Zhang, Zhang; Qian, Bo (Synthesis, 2022)
A simple continuous flow microreactor was successfully constructed for the N-oxidation of pyridine. The continuous flow microreactor used titanium silicalite (TS-1) in a packed-bed microreactor and H2O2 (in methanol as solvent) as the catalytic oxidation system for the formation of various pyridine N-oxides in up to 99% yields. This process is a safer, greener, and more highly efficiency process than using a batch reactor. The device was used for over 800 hours of continuous operation with the catalyst maintaining great activity thus providing great potential for large-scale production.
Keywords: continuous flow microreactor; hydrogen peroxide; N-oxidation; pyridine; green synthesis; titanium silicalite